1992
DOI: 10.1029/92jd00254
|View full text |Cite
|
Sign up to set email alerts
|

Surface flux measurements in FIFE: An overview

Abstract: In 1987 the Surface Flux Group of the first ISLSCP Field Experiment (FIFE) operated 22 stations at 20 sites. In 1989, 13 sites were instrumented. A variety of sensors were employed to calculate the fluxes of mass and energy. An effort was made throughout the FIFE campaign to compare sensors. A series of papers in this special issue present these group studies and efforts. These papers principally report the 1987 campaign, although two papers report station intercomparison during 1989. Additional papers examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(43 citation statements)
references
References 25 publications
0
42
0
1
Order By: Relevance
“…The problem was more evident during the land surface experiments at the end of the 1980s such as the First International Satellite Land Surface Climatology Project (ISLSCP) Field Experiment (FIFE) (Kanemasu et al 1992). While the cause was first thought to be in the eddy-covariance measurements, later studies discussed problems with the radiation measurements (Koitzsch et al 1988) and the storage in the canopy and the upper soil layer (Foken 1990;Bolle et al 1993;Braud et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The problem was more evident during the land surface experiments at the end of the 1980s such as the First International Satellite Land Surface Climatology Project (ISLSCP) Field Experiment (FIFE) (Kanemasu et al 1992). While the cause was first thought to be in the eddy-covariance measurements, later studies discussed problems with the radiation measurements (Koitzsch et al 1988) and the storage in the canopy and the upper soil layer (Foken 1990;Bolle et al 1993;Braud et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In most of the land-surface experiments (Bolle et al 1993;Kanemasu et al 1992;Laubach and Teichmann 1996;Oliphant et al 2004;Oncley et al 2007;Tsvang et al 1991) and also in the carbon dioxide flux networks Wilson et al 2002), a closure of the energy balance of approximately 80% was found. An experiment specifically designed to investigate this problem, the Energy Balance Experiment 2000 (EBEX-2000), took place in the summer of 2000 near Fresno, CA.…”
mentioning
confidence: 99%
“…The discussion was a logical successor to a workshop held in 1994 in Grenoble, France (Foken and Oncley 1995), where the problem of the unclosed surface energy balance-which is where the observed turbulent fluxes of sensible and latent heat do not sufficiently account for the measured net available energy at the Earth's surface-was addressed after energy budget closure analyses in the 1980s and early 1990s (Bolle et al 1993;Kanemasu et al 1992;Koitzsch et al 1988;Laubach and Teichmann 1996;Leuning et al 1982;Tsvang et al 1991). Many of the issues addressed in the 1994 workshop formed the scientific hypothesis for the special Energy Balance Experiment ( EBEX-2000;Oncley et al 2007), but this campaign did not yield a complete solution to the problem.…”
mentioning
confidence: 99%